Electronic participation with a special reference to social media - a literature review - Alarabiat, Ayman (2016)
As a consequence of the interdisciplinary nature of Electronic Partici-pation (e-Participation), current research on the field is fragmented and scattered. The exciting blurry boundaries and the immature identity of the field are making difficult the understanding of the main domain themes being investigated, in par-ticular for “neophytes” researchers. In practice, several e-Participation initiatives often attract a wide audience but face serious limitations regarding involvement of those who attract. Recently, the potential of using social media to address cit-izens’ involvement deficit has been subject of academic debate. By consulting 44 e-Participation papers, considered highly relevant to the aforementioned chal-lenges, this paper produces a general overview of e-Participation research, par-ticularly through social media. The findings show that the e-Participation field still faces the challenge of identity and strive for gaining wider recognition as an independent research area. Concerning e-Participation through social media which seems to be partly overlooked in the field research, the politicians-citizen’s interaction has dominated scholars' attention and the adoption of such initiatives sponsored and driven by governments are rarely examine. Based on the findings, several research suggestions, which could play a significant contribution to advance future e-Participation research, are proposed.